Dilatation parameterization for two-dimensional modeling of nearly incompressible isotropic materials - Eskandari, Hani; Goksel, Orcun; Salcudean, Septimiu E; Rohling, Robert (Physics in medicine & biology, 2012)
A new method to model the stress-strain relationship in two dimensions is proposed, which is particularly suited for analyzing nearly incompressible materials, such as soft tissue. In most cases of soft tissue modeling, plane strain is reported to approximate the deformation when an external compression is applied. However, it is subject to limitations when dealing with incompressible materials, e.g., when solving the inverse problem of elasticity. We propose a novel 2D model for the linear stress-strain relationship by describing the out-of-plane strain as a linear combination of the two in-plane strains. As such, the model can be represented in 2D while being able to explain the three-dimensional deformation. We show that in simple cases where the applied force is dominantly in one direction, one can approximate the sum of the three principal strain components in a plane by a scalar multiplied by the out-of-plane strain. 3D finite-element simulations have been performed. The proposed model has been tested under different boundary conditions and material properties. The results show that the model parametrization is affected mostly by the boundary conditions, while being relatively independent of the underlying distribution of Young's modulus. An application to the inverse problem of elasticity is presented where a more accurate estimate is obtained using the proposed dilatation model compared to the plane-stress and plane-strain models.